Crude Oil Exploration in the World - Abdel-Aziz Younes, Mohamed (IntechOpen, 2012)
"Crude Oil Exploration in the World" contains multidisciplinary chapters in the fields of prospection and exploration of crude oils all over the world in addition to environmental impact assessments, oil spills and marketing of crude oils.